Improved performance of polyimide Cirlex-based dielectric barrier discharge plasma actuators for flow control - Nunes-Pereira, E. J. (2022)
Dielectric barrier discharge (DBD) plasma actuators are simple electrohydrodynamic devices, which are able to provide effective aerodynamic control. One of the main components of these devices is the thin dielectric layer, which allows to separate and prevent the arc between the high voltage electrodes. Different materials can be used as dielectric layer to reduce the power consumption or boost the flow controlling effect of the actuators. In this context, this report presents a comparative study of two commercial polyimides, Kapton and Cirlex, used as dielectric layer of surface DBD plasma actuators. The electrical, dielectric, mechanical, electromechanical and thermal properties were obtained to evaluate overall performance. It was verified that Cirlex (8.3 W) consumes less power than Kapton (21.3 W) to generate higher induced flow velocity of ≈3.4 m/s for an input voltage of 11 kVpp and 24 kHz. During one AC cycle at 11 kVpp the charge transferred for Cirlex (70 nC) is lower than for Kapton (100 nC), as well as the dielectric breakdown voltage to ignite the plasma discharge, 1.5 and 2.2 kVpp, respectively. The Cirlex DBD presents a higher voltage operation limit (at least 14 kVpp) and a more regular plasma discharge, which results in a more homogenous thermal profile and temperature distribution during its operation. The Cirlex actuator delivered higher mechanical power (6.2 mW) and achieved higher electromechanical efficiency (0.004%). The polyimide Cirlex proved to be a suitable alternative for Kapton to fabricate DBD plasma actuators for flow control with improved performance.